2015
DOI: 10.12669/pjms.315.8411
|View full text |Cite
|
Sign up to set email alerts
|

Use Supravital Toluidine Blue Staining to Improve the Efficiency of Fine-Needle Aspiration Cytology Reporting in Comparison to Papanicolaou Stain.

Abstract: Objective:To see the efficiency, adequacy and accuracy of toluidine blue stained smears of FNAC of Breast thyroid and salivary glands swelling with comparison to conventional stained FNAC smears with Papanicolaou.Methods:A total of 114 aspirates from various sites were included in the study. The smears were stained with toluidine blue and conventional Papanicolaou stain and the cytomorphology of both the smears were compared. The values were tabulated and statistical tests of significance was applied.Results:O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Moreover, the percentage of inadequacy was reduced to just 25%. 12 In 2012, Ammanagi et al showed that onsite TBS and screening improved the efficiency of FNAC reporting. 13 Various researchers like Miller et al, Onofre et al, Mashberg, and Hedge et al showed in their respective articles TBS as diagnostic adjunct in detection of asymptomatic oral squamous cell carcinoma and its utility in early detection of oral malignancies.…”
Section: Granulomatous Lesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the percentage of inadequacy was reduced to just 25%. 12 In 2012, Ammanagi et al showed that onsite TBS and screening improved the efficiency of FNAC reporting. 13 Various researchers like Miller et al, Onofre et al, Mashberg, and Hedge et al showed in their respective articles TBS as diagnostic adjunct in detection of asymptomatic oral squamous cell carcinoma and its utility in early detection of oral malignancies.…”
Section: Granulomatous Lesionmentioning
confidence: 99%
“…It is easily available, very cheap, cost-effective, and used for quick reporting. 12 Many of the studies with TBS were done on fine-needle aspiration cytology (FNAC) and oral mucosal lesions. TBS has also been used earlier by several researchers in their study for Rapid Onsite Evaluation (ROSE) on different sites like lymph nodes, thyroid, breast, and salivary glands.…”
Section: Introductionmentioning
confidence: 99%
“…3 TBS has been extensively used by various researchers as a vital stain for oral mucosal lesion and aspiration cytology reporting in recent years. [3][4][5] The literature shows, TBS is a practical, rapid, inexpensive and effective adjunct diagnostic tool. [4][5][6] Toluidine blue is supravital stain that accentuates good cytological and nuclear details and enables the three dimensional view of cells in wet mount film.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The literature shows, TBS is a practical, rapid, inexpensive and effective adjunct diagnostic tool. [4][5][6] Toluidine blue is supravital stain that accentuates good cytological and nuclear details and enables the three dimensional view of cells in wet mount film. It is easily available, very cheap, cost effective and used for quick reporting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation